Systematic development and characterization of curcumin-loaded nanogel for topical application - Kesharwani P.; Jain A.; Srivastava A.K.; Keshari M.K. (My University, 2025)
Curcumin (CUR) conventional formulation has poor oral bioavailability due to low solubility and low stability. Also, it extensively undergoes first-pass-metabolism showing low biological activity. The present work focuses on the systematic development and characterization of CUR-loaded Nanostructured Lipid Carrier (CUR-NLCs) having promising topical applications for skin diseases such as psoriasis. CUR-NLCs were prepared by using high-speed homogenization method. Quality by design approach was exploited to select out Critical Process Parameters i.e. homogenization speed (X1), homogenization time (X2), amount of lipid (X3), solid lipids (SL): liquid lipids (LL) (X4), and surfactant conc. (X5) using Plackett–Burman design and for obtaining critical quality attributes i.e. particle size (Y1) and entrapment efficiency (Y2) using Box–Behnken design. The developed NLCs were found to be nano-metric in size (189.4 ± 2.6 nm) with a low polydispersity index (0.262 ± 0.24), zeta potential (-21.45 ± 1.3 mV), and showed good encapsulation efficiency (86.72 ± 09%). Surface morphology determined by SEM and AFM revealed the spherical shape of the NLCs with a smooth surface. XRD studies showed NLCs in the amorphous state. After incorporation of NLCs into a nanogel, it was characterized for pH, rheological behavior, spreadability, in vitro occlusion, and in vitro release kinetics. The drug release from NLC in 24 h was found to be 60.2 ± 0.45% indicating a sustained release pattern. Ex vivo permeation studies revealed a good permeation flux (0.453 ± 0.76 µg/cm2.h) and retention (60.2 ± 0.45%) of CUR in the skin epidermis. Thus, developed CUR-NLCs can be a potential delivery system and a promising therapeutic approach for the effective treatment of psoriasis. © 2020, © 2020 Informa UK Limited, trading as Taylor & Francis Group.